Charge-to-Alanine Mutagenesis of the Adeno-Associated Virus Type 2 Rep78/68 Proteins Yields Temperature-Sensitive and Magnesium-Dependent Variants - Gavin, Denise K. (American Society for Microbiology, 1999)
The adeno-associated virus type 2 (AAV) replication (Rep) proteins Rep78 and 68 (Rep78/68) exhibit a number of biochemical activities required for AAV replication, including specific binding to a 22-bp region of the terminal repeat, site-specific endonuclease activity, and helicase activity. Individual and clusters of charged amino acids were converted to alanines in an effort to generate a collection of conditionally defective Rep78/68 proteins. Rep78 variants were expressed in human 293 cells and analyzed for their ability to mediate replication of recombinant AAV vectors at various temperatures. The biochemical activities of Rep variants were further characterized in vitro by using Rep68 His-tagged proteins purified from bacteria. The results of these analyses identified a temperature-sensitive (ts) Rep protein (D40,42,44A-78) that exhibited a delayed replication phenotype at 32°C, which exceeded wild-type activity by 48 h. Replication activity was reduced by more than threefold at 37°C and was undetectable at 39°C. Stability of the Rep78 protein paralleled replication levels at each temperature, further supporting a ts phenotype. Replication differences resulted in a 3-log-unit difference in virus yields between the permissive and nonpermissive temperatures (2.2 × 10(6) and 3 × 10(3), respectively), demonstrating that this is a relatively tight mutant. In addition to the ts Rep mutant, we identified a nonconditional mutant with a reduced ability to support viral replication in vivo. Additional characterization of this mutant demonstrated an Mg(2+)-dependent phenotype that was specific to Rep endonuclease activity and did not affect helicase activity. The two mutants described here are unique, in that Rep ts mutants have not previously been described and the D412A Rep mutant represents the first mutant in which the helicase and endonuclease functions can be distinguished biochemically. Further understanding of these mutants should facilitate our understanding of AAV replication and integration, as well as provide novel strategies for production of viral vectors.